Penyimpangan Maksim Kesopanan Dalam Video “Mbambong” Di Youtube Woko Channel - Alifia Risnadian Aulia; Wendy Febia Nuricahyati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Deviations from the principles of politeness by speech participants are generally due to the desire to achieve a speech. The implicit meaning of speech can have a positive or negative meaning, depending on the context and circumstances when the speech occurs. The purpose of this deviation is, for example, to ridicule, humiliate, show antipathy, and so on, the purpose of which is to harm other people. This research is entitled Deviations from the Maxim of Politeness in the